Arah Kebijakan Hukum Politik Ekonomi - Mardalena Hanifah (Jurnal Ilmu Hukum, 2012)
Law and economics are the pillars of development so that both must be matched and aligned with the interests of the people. Thus the legal policy direction of economic policy should  be something that has value in order for legal purposes can be achieved.